Therapeutic effects of chitosan/β-glycerophosphate/collagen hydrogel combined with MSCs on chronic achilles tendon injury via the Akt/GSK-3β pathway - Songlin Liu; Liang Ma (Journal of Orthopaedic Surgery and Research)
Abstract Background Chronic Achilles tendon injuries, commonly resulting from inadequate management of acute incidents, significantly reduce patients’ quality of life. Current treatments, including conservative, surgical, and regenerative approaches, often yield suboptimal results. This study investigated the therapeutic effectiveness of a chitosan/β-glycerophosphate/collagen (C/GP/Co) hydrogel combined with bone marrow mesenchymal stem cells (MSCs) for chronic Achilles tendon injury in a rat model. Material & Methods A temperature-sensitive injectable C/GP/Co hydrogel was synthesized and combined with MSCs to treat a chronic Achilles tendon injury in Sprague–Dawley rats. The rats were divided into four groups receiving saline (model), C/GP/Co hydrogel, C/GP/Co/MSCs hydrogel, or normal control. After 6 weeks, morphological, biomechanical, and molecular assessments were conducted, including histology, Western blot analysis for protein expression, and the evaluation of the Akt/GSK-3β signaling pathway. Results The C/GP/Co/MSCs hydrogel significantly enhanced tendon healing compared to the model and C/GP/Co groups, as evidenced by improved collagen fiber organization and an increased type I/III collagen ratio on histological analysis. Western blot results revealed activation of the Akt/GSK-3β pathway by the C/GP/Co/MSCs hydrogel, leading to enhanced tendon cell proliferation and reduced apoptosis, demonstrated by a decreased Bax/Bcl-2 ratio and Caspase-3 expression. Downregulation of inflammation markers CD206 and CD163 was significant. Biomechanical testing indicated that the C/GP/Co/MSCs hydrogel restored tendon tensile strength closer to normal levels. Conclusions The C/GP/Co/MSCs hydrogel establishes a supportive microenvironment for MSC function, aiding tendon healing through the Akt/GSK-3β pathway. Its dual role in inflammation and apoptosis reduction, while enhancing biomechanical properties, demonstrates its potential as an innovative treatment for persistent Achilles tendon ailments. Future research endeavors should comprehensively explore the molecular pathways and assess their clinical applicability.